Sistem Informasi Pura Kahyangan Jagat Berbasis Ontology (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2022)
Bali is one of the tourist attractions that are in great demand by tourists both from foreign tourists and from within the country because it has a diversity of arts and culture. However, many people do not know the meaning of the temple itself and the types of temples. Therefore, in this study, the development of the Kahyangan Jagat Temple information system was carried out using the Prototyping method and using the ontology as the backbone of the system. The development of the ontology model is built using the Methodology method. The system has features of browsing and searching. In evaluating the system's functionality, a Black-Box Testing test of the browsing and search features was carried out. The results obtained in the system provide good functionality testing results.